2023
DOI: 10.3390/cancers15041308
|View full text |Cite
|
Sign up to set email alerts
|

Non-Parenchymal Cells and the Extracellular Matrix in Hepatocellular Carcinoma in Non-Alcoholic Fatty Liver Disease

Abstract: Hepatocellular carcinoma (HCC) in the setting of non-alcoholic fatty liver disease (NAFLD)-related cirrhosis and even in the pre-cirrhotic state is increasing in incidence. NAFLD-related HCC has a poor clinical outcome as it is often advanced at diagnosis due to late diagnosis and systemic treatment response is poor due to reduced immune surveillance. Much of the focus of molecular research has been on the pathological changes in hepatocytes; however, immune cells, hepatic stellate cells, liver sinusoidal endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 211 publications
0
11
0
Order By: Relevance
“…Activated hepatic gluconeogenesis also increases blood glucose levels. 36 High intrahepatic TGs and fasting blood glucose are the distinguishing features of diagnostic MAFLD pairs. Therefore, using the TyG index as a valid diagnostic indicator of MAFLD is logical.…”
Section: Discussionmentioning
confidence: 99%
“…Activated hepatic gluconeogenesis also increases blood glucose levels. 36 High intrahepatic TGs and fasting blood glucose are the distinguishing features of diagnostic MAFLD pairs. Therefore, using the TyG index as a valid diagnostic indicator of MAFLD is logical.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that stress-related signaling pathways, like c-Jun N-terminal kinase (JNK) and NF-κB, are activated by pro-inflammatory cytokines, such as TNF-α, IL-1, IL-6, STAT3, and ERK. This activation leads to increased hepatocyte proliferation and ultimately promotes the development of hepatocarcinogenesis [ 61 ]. HSCs that are not strongly activated generate growth factors and cytokines, including hepatocyte growth factor (HGF), which can help prevent hepatocyte death and the development of HCC [ 62 ].…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%
“…In addition, integrins, which act as cell surface mechanoreceptors, can interfere with TGF-β1 and PDGF and modulate the proliferation and survival of hepatocytes and HSC [ 65 ]. The regenerative repair pathways, such as the Hedgehog signaling pathway, are induced during the process of fibrogenesis in NASH and predict the induction of hepatocarcinogenesis [ 61 ].…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%
See 2 more Smart Citations